INCREASING THE RELIABILITY OF NAVIGATION TOOLS UNDER THE INFLUENCE OF VARIABLE TEMPERATURES FOR EFFICIENT OPERATION BY WATER TRANSPORT - Sapronov Оlexander; Sharanov, Vladyslav (Science-based technologies, 2025)
Thanks to advanced logistics, water transport transports an unlimited amount of various cargoes. Therefore, water transport is one of the world’s largest carriers. First, this is due to the extensive network of ports and sea routes, which allows transporting goods over long distances, including intercontinental ones. Therefore, ensuring global connectivity is critical to delivering goods on time. The work presents the technological aspects of improving the thermophysical characteristics of epoxy composite protective coatings to protect navigational means of water transport that operate under variable external factors. The polymerized ED-20 epoxy binder was used with PEPA polyethylene polyamine hardener to form epoxy composite protective coatings. The biocidal filler trimethoprim C14H18N4O3 (CAS: 738-70-5) was used to increase the thermophysical properties of polymeric materials, with a content of 5.0-30.0 pts.wt. Based on thermogravimetric (TGA) and differential thermal (DTA) analysis, the values of the critical parameters necessary to determine the temperature range at which it is possible to operate the developed epoxy composite coatings intended for the protection of navigation aids without changing their properties, in particular: the maximum temperature of the beginning of mass loss is – T0 = 609 K; relative mass loss – εm = 69%; the initial temperature of the exoeffect is Тinit = 488 K; the maximum value of the peak temperature of the exoeffect is Tmax = 550 K. A mathematical calculation of the values of the activation energy of thermal destruction was performed to determine the resistance to the destruction of chemical bonds under the influence of temperature. It has been proven that epoxy composite coatings filled with trimethoprim at a content of 15.0 pts.wt. are characterized by the maximum activation energy of Ea = 167 kJ/mol, which indicates the thermal stability of filled epoxy composite coatings. The course of physicochemical processes of thermal destruction of epoxy composite coatings filled with trimethoprim was determined by the method of IR spectral analysis. Based on complex studies using DTA, TGA, IR spectral analysis, and mathematical calculation of the activation energy, it was proved that the operating temperature range of the developed epoxy coatings should not exceed 488 K.